2010
DOI: 10.1103/physrevc.81.034604
|View full text |Cite
|
Sign up to set email alerts
|

Time scales in nuclear giant resonances

Abstract: We propose a general approach to characterise fluctuations of measured cross sections of nuclear giant resonances. Simulated cross sections are obtained from a particular, yet representative selfenergy which contains all information about fragmentations. Using a wavelet analysis, we demonstrate the extraction of time scales of cascading decays into configurations of different complexity of the resonance. We argue that the spreading widths of collective excitations in nuclei are determined by the number of frag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Recently, alternative methods have been developed based on a quantitative analysis of the fine structure of giant resonances observed in high-resolution inelastic scattering and charge-exchange reactions. These new methods for the extraction of such scales include the local scaling dimension approach [111], the entropy index method [114], and the use of wavelet techniques [115,116]. Of these, wavelet analysis has been established as a particularly successful approach [115].…”
Section: Characteristic Scales and Giant Resonance Decay Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, alternative methods have been developed based on a quantitative analysis of the fine structure of giant resonances observed in high-resolution inelastic scattering and charge-exchange reactions. These new methods for the extraction of such scales include the local scaling dimension approach [111], the entropy index method [114], and the use of wavelet techniques [115,116]. Of these, wavelet analysis has been established as a particularly successful approach [115].…”
Section: Characteristic Scales and Giant Resonance Decay Mechanismsmentioning
confidence: 99%
“…There are two types of information which can be extracted from the fine structure. Firstly, several methods have been developed aiming at a quantification of characteristic features of the fine structure [111,112,113,114,115,116], of which wavelet analysis was shown to be particularly promising [115]. By comparison with EDF calculations one is able to single out the relative importance of competing mechanisms [104] contributing to the total width of a giant resonance.…”
Section: Introductionmentioning
confidence: 99%
“…It could be shown that in this case the spreading width dominates over the escape width but the deduced scales depended strongly on the assumptions about the (unknown) number of doorway states. Later, new methods were proposed for the extraction of such scales based an a local scaling dimension approach [17,18,19], an entropy index method [20,21], and the use of wavelet techniques [22,23]. A comprehensive discussion of the advantages and limitations of the various methods concluded that wavelet analysis is most promising [24].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of theoretical approaches has been put forward to understand the fine structure including doorway-state analysis [7], a local scaling dimension model [8], an entropy index method [9] and wavelet analysis [10,11]. A comparison for representative cases indicates that a wavelet analysis is a particularly promising tool [12], since it provides simultaneously a quantitative measure of the fine structure and information on the localization in the excitation energy spectrum.…”
Section: Introductionmentioning
confidence: 99%